Research on microscopic features of salt rock being damaged via loading osmosis on the basis of CT scanning. Issue 5 (September 2019) - Zeng, Yin; Liu, Jianfeng; Li, Zhicheng; Xu, Huining; Wang, Lu; Zhang, Qiangxing
Abstract: In order to study the microscopic characteristics of the salt rock being damaged through diverse level of osmosis, CT scans are made to the salt rock before the osmosis loading and after it is damaged, in which the stress-strain is applied to the whole process. The differences of the micro-features of damaged salt rock are discussed. The experimental results show that: (1) the microscopic characteristics observed from CT scan indicate that the critical confining pressure of salt rock is 10MPa. When the confining pressure is lower than 10 MPa, shear crack can be seen obviously in the cross and longitudinal section of the salt rock, with the form of shear damage; While confining pressure is more than 10MPa, the fissure is short and the rock is damaged in a drum-shaped deformation; An impervious point occurs when it exceeds 10MPa. (2) The number of cracks demonstrates the intrinsic crack development of salt rock. The salt rock has a critical point (d=0.6mm) in the number of small cracks (d≤1mm). 0.6mm is the boundary point. When it is 0.6mm or less, the number of fissures in the salt rock with confining pressure of 5MPa is more than those with 10MPa. The larger the diameter of the fissure is, the closer the number of fissures with the above two confining pressures is. While boundary point is more than 0.6mm, it will have the opposite effect. (3) The internal mechanism of that the end effect has an impact on the osmosis evolution of salt rock is uncovered. Due to the stress-intensive effect at the ends, the development path of the small cracks gradually spreads from the both ends to the inside, therefore, the osmosis of the gas osmosis channels at the ends is hindered, resulting in a low salt rock permeability during the loading process.